1998
DOI: 10.1590/s0066-782x1998001100006
|View full text |Cite
|
Sign up to set email alerts
|

Estudo morfométrico do miocárdio em adultos com subnutrição protéico-energética

Abstract: Purpose - Estudo Morfométrico do Miocárdio em Adultos com Subnutrição Protéico-Energética Artigo OriginalA subnutrição protéico-energética (SPE) crônica, do tipo marasmo, decorre do aporte alimentar insuficiente para suprir as necessidades energéticas e protéicas do indiví-duo, processo que se acompanha de emagrecimento progressivo, com diminuição do peso corporal e das reservas de gordura e de massa muscular. Em adultos, a SPE do tipo kwashiorkor está associada com hipoalbuminemia e edema, geralmente com evol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…However, we also observed a positive and significant correlation between body weight and heart weight (r=0.65), and also between heart weight and body mass index (r=0.52), which indicates that the thinner the individual, the lower his heart weight is. Likewise, according to morphometric studies on myocardiocytes 5 , individuals with advanced malnutrition have greater degrees of heart hypotrophy 13 . This fact may have clinical repercussions, such as a prolonged QTc interval on the electrocardiogram 14 , a lower cardiac output 2 , and a higher risk of developing the refeeding syndrome, a condition in which cardiac decompensation would result from myocardial dysfunction associated with cardiac hypotrophy secondary to malnutrition 7 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we also observed a positive and significant correlation between body weight and heart weight (r=0.65), and also between heart weight and body mass index (r=0.52), which indicates that the thinner the individual, the lower his heart weight is. Likewise, according to morphometric studies on myocardiocytes 5 , individuals with advanced malnutrition have greater degrees of heart hypotrophy 13 . This fact may have clinical repercussions, such as a prolonged QTc interval on the electrocardiogram 14 , a lower cardiac output 2 , and a higher risk of developing the refeeding syndrome, a condition in which cardiac decompensation would result from myocardial dysfunction associated with cardiac hypotrophy secondary to malnutrition 7 .…”
Section: Discussionmentioning
confidence: 99%
“…Experiments with animals 2 and autopsies of malnourished children show that the heart undergoes hypotrophy proportional to the degree of weight loss 3,4 . Even though studies on heart morphometry and function of malnourished adults are rare 5 , experiments with animals suggest that the myocardium undergoes a milder wasting than striated skeletal muscles do, possibly due to the relative increase in vascularization and oxygenation of the myocardiocytes 6 . However, patients quite frequently develop tachycardia, hydric retention, and cardiac decompensation during nutritional therapy, and this phenomenon has been attributed to myocardial dysfunction associated with cardiac hypotrophy secondary to malnutrition 7 .…”
mentioning
confidence: 99%
“…Reversibility of lipopigment accumulation is not yet fully understood or proven, but recent studies have shown that in fish, up to 45% of lipopigment accumulation can be reverted due to recovery of lysosomal stability, knowing that the more polluted the area, the more efficient tissue regeneration gets (Au et al). On the other hand, the possibility of oxidation and consumption of lipofuscin's lipid components and protein components cannot be discarded (Cunha et al, 1998).…”
Section: Discussionmentioning
confidence: 99%